2022
DOI: 10.1186/s12889-022-12668-1
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to dietary guide for elderly adults and health risks of older adults in ethnic minority areas in China: a cross-sectional study

Abstract: Background The impact of dietary guidelines on health in ethnic minority regions needs to be further explored because of multiple sociocultural factors. Therefore, this study was conducted to analyze the association between adherence to dietary guidelines and health risks in an elderly population in an ethnic minority region. Methods A cross-sectional survey was conducted among 836 older adults in ethnic minority areas. They were asked to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several prior studies have analyzed the dietary intake in diabetic patients and their adherence to dietary guidelines where the dietary pattern and rate of adherence varied greatly in different study populations [ 9 , 10 , 11 ]. A few studies have analyzed the dietary adherence among diabetic populations in China, where most studies reported low adherence to dietary guidelines [ 12 , 13 ]. However, most of these studies had a small sample size and were not nationally representative.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies have analyzed the dietary intake in diabetic patients and their adherence to dietary guidelines where the dietary pattern and rate of adherence varied greatly in different study populations [ 9 , 10 , 11 ]. A few studies have analyzed the dietary adherence among diabetic populations in China, where most studies reported low adherence to dietary guidelines [ 12 , 13 ]. However, most of these studies had a small sample size and were not nationally representative.…”
Section: Introductionmentioning
confidence: 99%